The THE EFFECT OF DIABETES SELF MANAGEMENT EDUCATION (DSME) ON BLOOD SUGAR CONTROL IN TYPE 2 DIABETES PATIENTS (In Ngujuran Village) - Nurresta, Leni; Ryandini, Tiara Putri (jfpublisher, 2025)
Introduction Diabetes mellitussufferers have problem in controlling the increase in blood sugar levels,because it can trigger complication that will arise. Factors the affect blood sugar controlare age, physical activity, carbohydrate consumption, fiber consumption, stress and medication compliance. Diabetes Self Management Education(DSME) is one of the right action in converming blood sugarcontrol in type 2 diabetes mellitus sufferers. Thepupose of this study was todetermine the effect og diabetes self management education (DSME) on blood sugar control in type 2 diabetes mellitus patients in ngujuran village Methode This research design used in this study is quantitative “pre-experimental” using the research method “ one grup pre-post test design”with a time-cohort approach. The population of this study was 46 patients with type 2 diabetes mellitus in Ngujuran village who were selected using a simple random sampling technique, a sample of 42 patients with type 2 diabetes mellitus in Ngujuran village wa obtained. Result and Analysis. The results of the research carried out after analysis using the Wilcoxon test with a significance level of α=<0.05 obtained a value of = 0.000<0.05, which means that H1 is accepted, namely that there is an influence of diabetes self management education (DSME) on blood sugar control in type 2 diabetes mellitus patients in Ngujuran village. Discussion. From the description above, it can be concluded that diabetes self management education (DSME) has an effect on blood sugar control in patients with type 2 diabetes mellitus in Ngujuran village.